Effects of Visual Feedback on Balance and Risk of Fall among Geriatric Population - Mohamed, Shameer; Kumaresan, Abathsagayam; Surya, Vishnuram; Prathap, Suganthirababu; Vignesh, Srinivasan; Vinodhkumar, Ramalingam; Privadharshini, Kumar (INTI International University, 2023)
Introduction: Visual feedback training with a mirror is a technique that can improve postural stability by providing feedback on induced movements via a mirror image of the body image in the mirror. Balance training is considered to be an important aspect of a fall prevention program. Damage to balance ability causes difficulty in walking and performing functional activities. Hence, balance ability is the basis for independent movement and functional performance the aim is to find out the effects of visual feedback on balance and risk of fall among geriatric population. Aim and objectives: The aim and objective of the study is to find the effects of visual feedback on balance and risk of fall among geriatric population. Methodology: This study is an experimental study. A total of 30 geriatric population were selected based upon the inclusion and exclusion criteria. The participants were separated into two groups, the conventional group and the experimental group, each with 15 members. The detailed procedure was explained to the participants and a written informed consent form was obtained. Result: The values were statistically analyzed. The post-test mean value of Berg Balance scale in experimental group was 45.9 and conventional group was 43.2. This showed that Berg Balance Scale in experimental group was comparatively higher than conventional group. The post mean value of fall efficacy scale in experimental group was 4.80 and in conventional group was 5.93. This proves that fall efficacy scale in experimental group was comparatively less than conventional group. Conclusion: This study concluded that mirror visual feedback of experimental group was found more effective than conventional therapy in reducing risk of fall and increasing balance.